ANALISIS KOMPARATIF ABNORMAL RETURN SAHAM JII DAN NON JII SEBELUM DAN SESUDAH LIBUR IDUL FITRI (PERIODE 2009-2013) - Hasanuddin Hasanuddin (Universitas Mercu Buana, 2015)
Abstract: The purpose of this research is to examine differences between abnormal returnsbefore and after Idul Fitri holidays on Jakarta Islamic Index stock (JII) compared with shares isnot including the Jakarta Islamic Index stock (Non JII). This research is event study withcomparative analysis between abnormal return Jakarta Islamic Index stocks (JII) and that is notincluded in the Jakarta Islamic Index stocks (Non JII). The time of research is about five daysbefore Idul Fitri holidays and five days after the Idul Fitri holidays with period five years from2009 until 2013. The result of this research is the abnormal returns after Idul Fitri holidays ishigher than before the Idul Fitri holidays, both for JII stock and non JII . However, abnormalreturns JII stock and non JII is not difference with significant.Keywords : Idul Fitri holidays , Abnormal Return